Linking allostatic load, heart rate variability and brain functional networks and structures in healthy men - Solano-Atehortua, Juan M.; Castrillón, Gabriel; Suarez-Revelo, Jazmin X.; Sánchez-López, Juan D.; Vargas-Tejada, Daniel A.; Valentina, Hawkins Caicedo; Calderón, Juan C.; Gallo-Villegas, Jaime; Ospina-Serrano, Yedselt V.; Caicedo-Jaramillo, Juan D.; Miranda-Angulo, Ana L. (Psychoneuroendocrinology, 2026)
Introduction The allostatic load index (ALI) measures the cumulative physiological burden exerted on the body by chronic stress known as allostatic load (AL). The relationship between ALI and heart rate variability (HRV), as well as the brain moderation effect on this relationship in healthy individuals, is underexplored. Methods In this cross-sectional study of 88 healthy men (21–40 years) from Medellín, Colombia, we calculated two ALIs composed of four and seven biomarkers (ALI-4 and ALI-7) using a quartile-based risk summation method. Functional and structural neuroimaging metrics were derived from magnetic resonance imaging. Multiple linear regression models were used to evaluate the associations between the ALIs and HRV metrics derived from a 24-hour Holter. Exploratory interaction models tested whether the functional connectivity strength (FCS) of default mode (DMN), salience (SN) and control subnetworks (CEN), their cortical thickness as well as the volume of subcortical structures, moderated the ALI–HRV association. Results ALI-7 was positively associated with the LF/HF ratio (β = 0.09, p = 0.004, 95 % CI = 0.03–0.15). Exploratory interactions suggested that ALI-7’s association with the standard deviation of the NN intervals (SDNN) was moderated by the FCS in the posterior DMN and by cortical thickness in the anterior SN. However, none of these interactions remained significant after false discovery rate correction. Conclusion In healthy men, higher ALI was associated with reduced HRV as indicated by higher LF/HF ratio. Larger studies, including women, are needed to confirm the predictive value of ALI-7 and to elucidate the brain moderation effect on the AL-HRV relationship.
CRIS-Team Scopus Importer:2026-01-30
Keywords: Allostatic interoceptive network; Allostatic load index; Autonomic nervous system; Chronic stress; Large-scale resting state networks; Sympathovagal quotient